The effect of Ruscus Hyracanus extract on physicochemical, microbial and organoleptic properties of kefir: The effect of Ruscus Hyracanu on properties of kefir - sedaghati, marjaneh; Emtyazjoo, Mozhgan (Indian Journal of Dairy Science, 2024)
Kefir is a traditional functional fermented drink with acidic-alcoholic properties. In this study, the effect of Ruscus hyrcanus extract (0, 0.25%, and 0.5%) on the physicochemical, microbial, and sensory properties of kefir during 20 days of storage was evaluated. Total phenolic content (TPC) and antioxidant activity (AO) were evaluated using Folin-Ciocalteu, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) techniques. The results revealed that the stability and viscosity of kefir samples containing Ruscus hyrcanus extract were higher than control samples. Increasing the amounts of Ruscus hyrcanus extract had a significant effect on the TPC, AO, and lactic acid (LAB) numbers of enriched kefir (P˂0.05). The presence of Ruscus hyrcanus extract had a significant effect on the L* values of kefir (P˂0.05). In general, a kefir sample containing 0.5% Ruscus hyrcanus extract was more acceptable in comparison with the other samples on the 20th day of storage.